2005
DOI: 10.1017/s1752756200011224
|View full text |Cite
|
Sign up to set email alerts
|

Responses of lactating dairy cows to sodium bicarbonate or sodium bentonite in low forage diet

Abstract: Dietary sodium bicarbonate or sodium bentonite has been used in lactating cow diets to aid ration adjustment. Addition of sodium bicarbonate increased intake and milk production for cows fed high concentrate diets in the first two months after parturition (Erdman et al., 1980). Addition of dietary buffers such as sodium bicarbonate and sodium bentonite increased molar percentage of acetate and reduced propionate in dairy cows. Milk fat percentage was increased by sodium bicarbonate in dairy cows when fed low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Bentonite is one of the common natural clays used in animal diets to improve feed intake, digestibility of nutrients and daily gain (Saleh et al, 1999 andSalem et al, 2001). Mesgaran (2005) indicted that addition of sodium bentonite (350 g/cow/d) to the low forage diet slightly enhanced milk yield of Holstein cows. Katsoulos et al (2006) found that when cows were fed on concentrate ration supplemented with 1.25% clinoptilolite could be produced higher total milk yield than the unsupplemented ones.…”
Section: Introductionmentioning
confidence: 99%
“…Bentonite is one of the common natural clays used in animal diets to improve feed intake, digestibility of nutrients and daily gain (Saleh et al, 1999 andSalem et al, 2001). Mesgaran (2005) indicted that addition of sodium bentonite (350 g/cow/d) to the low forage diet slightly enhanced milk yield of Holstein cows. Katsoulos et al (2006) found that when cows were fed on concentrate ration supplemented with 1.25% clinoptilolite could be produced higher total milk yield than the unsupplemented ones.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Sulzberger et al (2016) pointed that when dairy cows fed on TMR with high grain challenge and supplemented with 0.5, 1 and 2% clay (on DM basis) milk yield tended to increase than the unsupplemented once. Mesgaran (2005) found that the addition of 305g sodium bentonite/cow/day to the low forage diet slightly enhanced milk yield of Holstein cows. Abd El-Baki et al (2001) studied the effect of clays on animal nutrition and some physiological blood parameters.…”
Section: Introductionmentioning
confidence: 95%
“…The additives of Bentonite were safety for feeding livestock as 20 mg/Kg intake DM for all animal species (EFSA, 2013). On the other hand, Mesgaran (2005) showed that addition of 350 g bentonite/cow/day to the low forage diet slightly improved the production performance specially milk yield of Holstein cows. Katsoulos et al (2006) found that when cows fed on concentrate ration supplemented with 1.25% clinoptilolite could be produced higher total milk yield than unsupplemented diets.…”
Section: Introductionmentioning
confidence: 97%